Mechanism of hydroxysafflor yellow A on acute liver injury based on transcriptomics - Hou, Xiangmei; Zhang, Ziying; Ma, Yuehong; Jin, Rong; Yi, Bing; Yang, Dongdong; Ma, Lijie (Frontiers in Pharmacology, 2022)
Objective: To investigate the effect of Hydroxysafflor yellow A (HSYA) on acute liver injury (ALI) and explore its potential transcriptional regulation mechanism. Methods: In this current study, an acute rat liver injury model was established with carbon tetrachloride (CCl4), liver morphology was observed and liver indexes were detected of rats after dissection, and assessed the effect of HSYA on the liver of model rats by hematoxylin and eosin (HE). Additionally, we performed transcriptome analysis using RNA-sequencing (RNA-seq) technology, including cluster, Gene Ontology (GO), and pathway analyses, to identify differentially expressed genes (DEGs). Finally, the most differentially expressed DEGs identified in the RNA-Seq analysis were verified by real-time quantitative PCR (qRT-PCR). Results: HSYA effectively alleviated CCl4-induced ALI, including observations of improved liver function, oxidative stress and inflammation were significantly reduced. Moreover, we identified upregulated and downregulated DEGs in the model group relative to the control and HSYA groups, six of these genes were verified by qRT-PCR, including Tymp, Fabp7, Serpina3c, Gpnmb, Il1r1 and Creld2, indicated that these genes were involved in the regulation of HSYA in ALI model. Membrane rafts, membrane microdomains, inflammatory response, regulation of cytokine production, monooxygenase activity and iron ion binding were significantly enriched in GO analysis. KEGG analysis showed that DEGs were mainly enriched in retinol metabolism, PPAR, NF-kappa B and NOD-like receptor signaling pathways. Conclusions: HSYA can improve liver function, inhibit oxidative stress and inflammation, improve the degree of liver tissue damage. The RNA-Seq results further verified that HSYA has the characteristics of multiple targets and multiple pathways, and to protect the liver from damage by regulating the expression of Tymp, Fabp7, Serpina3c, Gpnmb, Il1r1, Creld2 and other genes as well as the retinol metabolism, PPAR, NF-kappa B and NOD-like receptor signaling pathways.